A REVIEW ON CHITRAKA WITH ITS MEDICINAL PROPERTIES W.S.R TO ITS AMA PACHAN AND AGNI DEEPANA ACTION - Chhavi, *Yadav; Suresh, Chaubey; Tejbeer, Singh; Lakhan, Rohilla (International Journal of Ayurveda and Pharma Research, 2017)
If we talk about Ayurveda, Science of life, the concept of AMA is unique. Ama is a Sanskrit word that translates literally to mean things like "unripe," "uncooked," "raw," "immature," or "undigested. Essentially, it is a form of un-metabolized waste that cannot be utilized by the body.To some degree, the formation of small amounts of Ama is a normal part of the digestive process, provided it is efficiently removed. But when it is not regularly cleared and eliminated, ama becomes hugely problematic. In fact, Ama is said to be the root cause of all disease, and Amaya, a Sanskrit word for disease literally means "that which is born out of Ama. The connection between Ama and the disease process makes perfect sense because the qualities of Ama are in direct opposition to those of Agni. Strong Agni is essential to the maintenance of proper health. In other words, when Agni is compromised and when Ama accumulates, our health suffers, and the two situations are mutually reinforcing. In Ayurveda, the concept of Agni, is of central importance. In fact, the strength of Agni in the body is among the most critical factors in determining overall health. By contrast, Ama is a toxic, disease causing substance that forms as a result of impaired Agni, and that, in turn, destroys Agni. In this way, impaired Agni and the creation of Ama routinely enter into a vicious and self-perpetuating cycle. Unfortunately, the accumulation of Ama is extremely detrimental to our health; it can lead to all kinds of imbalances and is a causative factor in any number of diseases. Ama pachan and Agni Deepana is the best concept to improve all heath issues, for this the wonderful drug Chitraka is mentioned in our Ayurvedic texts. Here in this article we are going to discuss about Chitrak & its medicinal aspect as mentioned in Ayurvedic texts.